(untitled) (Nordic Journal of African Studies, 2010)
Previously, there has been a lack for an automatic analyser and generator for the word forms of Runyakitara. In this paper, we present a computational model for grammatical Runyakitara verbs. This model, RUNYAGRAM, is based on freely-available open-sourced finite-state methods and, in particular, the fsm2 interpreter. It captures the morphotactic structures with non-recursive context -free grammars supported by fsm2 and morpho-phonological alternations with a finite composition of commonly used context-dependent string rewriting rules. Their combination results into a finite state transducer that can be exported and used in numberless software-developing platforms. The obtained transducer is an important building-block that can be employed in comprehensive morphological analysers, syntactic parsers, spell-checkers, text-to-speech synthesizers, and machine translation systems. Currently, 86% of the verb forms are recognized. It is possible to increase the coverage, or alternatively, to adapt the approach of the RUNYAGRAM system to related languages.